Recommendations for communicating evidence or research results relevant to decision making in public health: Lessons from a qualitative study carried out in Colombia during the COVID-19 pandemic (2023)
This working paper brings together a series of recommendations intended to facilitate collaborative work between academic researchers and public health decision makers in contexts of health emergency. The recommendations are drawn from the qualitative part of the COLEV project, an interdisciplinary research initiative hosted by the Universidad de los Andes and funded by the Canadian government’s International Development Research Center (IDRC) and the Swedish International Development Cooperation Agency (SIDA). Spanish versión: http://hdl.handle.net/1992/66226